2010
DOI: 10.3390/nu2101060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Glycemic Index of Carbohydrates on Acne vulgaris

Abstract: Acne vulgaris may be improved by dietary factors that increase insulin sensitivity. We hypothesized that a low-glycemic index diet would improve facial acne severity and insulin sensitivity. Fifty-eight adolescent males (mean age ± standard deviation 16.5 ± 1.0 y and body mass index 23.1 ± 3.5 kg/m2) were alternately allocated to high or low glycemic index diets. Severity of inflammatory lesions on the face, insulin sensitivity (homeostasis modeling assessment of insulin resistance), androgens and insulin-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
3
22
2
Order By: Relevance
“…Thus, promote inflammatory responses in the body. 10 This study is in line with a study by Çerman et al 13 which shows no significant difference between milk and acne vulgaris subgroups (mild acne, moderate acne and severe acne) (p=0.596, p>0.05). Besides, the study also shows no significant association between dairy product consumption among acne vulgaris and control groups (p=0.911, p>0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, promote inflammatory responses in the body. 10 This study is in line with a study by Çerman et al 13 which shows no significant difference between milk and acne vulgaris subgroups (mild acne, moderate acne and severe acne) (p=0.596, p>0.05). Besides, the study also shows no significant association between dairy product consumption among acne vulgaris and control groups (p=0.911, p>0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of an inverse relationship between dietary GL based on total and available carbohydrates and serum SHBG concentrations was consistent with results from a previous dietary intervention trial where SHBG was considerably lowered after a 12-week high-GL diet compared with the baseline, and significantly decreased compared with those on a low-GL diet, 15 although another study contrasting low-GI and high-GI diets did not find significant differences in SHBG after an 8-week intervention. 33 This somewhat contradicted the fact that in the present analysis dietary GI based on total or available carbohydrates was significantly associated with SHBG concentrations, although only before correction for multiple comparisons. Mechanistically, it has been suggested that a high-GL or -GI diet induces greater insulin production, and insulin could act as an inhibitor of hepatic synthesis of SHBG.…”
Section: Discussioncontrasting
confidence: 89%
“…In the past, nutrition was not a proven cause of acne. However, recent publications show a link between some dietary factors and acne . Nowadays, main food classes considered triggering acne are dairy products (especially skim milk) and hyperglycaemic carbohydrates …”
Section: Resultsmentioning
confidence: 99%
“…However, recent publications show a link between some dietary factors and acne. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Nowadays, main food classes considered triggering acne are dairy products (especially skim milk) and hyperglycaemic carbohydrates. 10,[29][30][31][32][33][34][35][36][37] An average regimen of dairy products has been reported impacting on acne, and one paper indicated that cow milk impacts on acne after already two glasses per day.…”
Section: Acne Exposome Factorsmentioning
confidence: 99%